Effect of SBR rubber particle size distribution on its thermo-mechano-chemical regeneration - Macsiniuc Adrian et al. (Progress in Rubber,Plastics and Recycling Technology, 2013)
Recycled Styrene-Butadiene Rubber(SBR)from ground tire rubber(GTR) was sieved into four granulometric fractions between 125 and 500 microns to determine the effect of particle size on its thermo-mechano-chemical regeneration in an internal batch mixer.Different temepratures(140-180 C)and roter speeds(40-120rpm) were imposed with and without the addition of a regeneration aid(aromatic oil).The results show that partial regeneration(lower crosslinking degree)is possible under specific thermo-mechanical conditions,but the addition of the aromatic oil has limited efficiency towards this regeneration.
Keywords: Aromatic oil; Crosslink density; Particle size distribution; Rubber regeneration; SBR